Invasive Management of Acute Myocardial Infarction Complicated by Cardiogenic Shock: A Scientific Statement From the American Heart Association. Issue 15 (13th April 2021) - Henry, Timothy D.; Tomey, Matthew I.; Tamis-Holland, Jacqueline E.; Thiele, Holger; Rao, Sunil V.; Menon, Venu; Klein, Deborah G.; Naka, Yoshifumi; Piña, Ileana L.; Kapur, Navin K.; Dangas, George D.
Abstract : Cardiogenic shock (CS) remains the most common cause of mortality in patients with acute myocardial infarction. The SHOCK trial (Should We Emergently Revascularize Occluded Coronaries for Cardiogenic Shock) demonstrated a survival benefit with early revascularization in patients with CS complicating acute myocardial infarction (AMICS) 20 years ago. After an initial improvement in mortality related to revascularization, mortality rates have plateaued. A recent Society of Coronary Angiography and Interventions classification scheme was developed to address the wide range of CS presentations. In addition, a recent scientific statement from the American Heart Association recommended the development of CS centers using standardized protocols for diagnosis and management of CS, including mechanical circulatory support devices (MCS). A number of CS programs have implemented various protocols for treating patients with AMICS, including the use of MCS, and have published promising results using such protocols. Despite this, practice patterns in the cardiac catheterization laboratory vary across health systems, and there are inconsistencies in the use or timing of MCS for AMICS. Furthermore, mortality benefit from MCS devices in AMICS has yet to be established in randomized clinical trials. In this article, we outline the best practices for the contemporary interventional management of AMICS, including coronary revascularization, the use of MCS, and special considerations such as the treatment of patients with AMICS with cardiac arrest. Abstract : Supplemental Digital Content is available in the text.